THE IMPACTS OF MODERNIZATION ON ECONOMICAL LIFE OF THE INDIANS: A STUDY ON JAMES FENIMORE COOPER’S THE PRAIRE - . Suparman (Humaniora, 2007)
This research is primarily aimed at revealing the impacts of modernization on economical life of the Indians in Cooper’s The Prairie. The study uses interdisciplinary approach, which involves economical, historical, cultural, and ecological approaches, besides mimetic approach. The analysis shows that modernization does not only cause positive impacts but also negative impacts, which are stronger. The bad impacts include monopoly, human and cultural conflict, poverty, disharmony, social injustice of mixed marriage, greediness, kidnapping, law breaking, materialistic life, adultery, divorce, and less religiosity. The positive impacts include independence, adaptation, rationality, and efficiency. The problems appear in the novel reflect the inner conflict of the author (Cooper himself). He questions the ideas of modernization brought by immigrants on the Indian land. To him, modernization can only be enjoyed by the upper class of the society. It cannot meet the necessity of the traditional people. The Indians loose some benefits because of the settlement of the immigrants in their land.